A systematic review of literature on occupational health and safety interventions for older workers. - Bentley T; Onnis L-A; Vassiley A; Farr-Wharton B; Caponecchia C; Andrew C; O'Neill S; De Almeida Neto A; Huron V; Green N (Taylor and Francis Group, 2023)
As the global population ages there is an imperative to enhance labour participation of older workers in ways that support good physical and psychological health. However, there is limited guidance for organisations on how to do this effectively. This systematic review examined literature identified through four databases and a targeted web-search, yielding 39 PRISMA records (32 scholarly, seven grey literature) reporting workplace interventions aimed at improving the injury outcomes of older workers. The review revealed that organisational and composite interventions may be most effective, although an absence of robust research in this area and a scarcity of empirical evidence-based interventions known to improve injury outcomes for older workers was noted. Responding to these shortcomings, this article presents 'A future research agenda for older worker health, safety and well-being interventions.' This systems-based approach has a dual focus on organisational and composite interventions combined with robust research design.Practitioner summary: We conducted a systematic literature review of studies focussed on workplace interventions to improve the physical and psychological safety of older workers. Within the existing literature, evidence for effective interventions and guidance for organisations is weak. We present a future research agenda with a systems approach to address these gaps.
Keywords: Older workers; ageing workforce; intervention; psychological injury; work-related musculoskeletal disorders; Humans; Occupational Health; Workplace